PENILAIAN POSTUR KERJA OPERATOR PACKAGING PABRIK DX PT. BRIDGESTONE SUMATRA RUBBER ESTATE - Gaustama Putra; Suci Ayu Lestari (Jurnal Optimalisasi, 2019)
The role of labor is an important factor in industrial activity because it affects the quality and quantity of output produced products. When doing activities, there is an interaction between the operator and the machine used. Knowing the operator's work posture to see the suitability when there is an interaction between work and work equipment used. Thus we can find out how the operator works correctly or not so that the level of fatigue, risk of illness, or even work accidents can be minimized to a minimum. In this study the RULA and REBA methods are used to assess the operator's work posture and get conclusions from the results of the work posture assessment in order to provide an idea of the right attitude and work position for the operator to avoid the risk of accidents and fatal fatigue in the packaging section of the factory processing department DX at PT. Bridgestone Sumatra Rubber Estate. Using the RULA method, the main score from the operator's work posture checks the surface contamination of bale 6 and the bale wrapping with plastic bags is 7, for the REBA method the operator of surface contamination bale 6 checks 10 and the bale wrapping operator with plastic bags is 8. From the grand value of RULA and REBA levels of risk of musculoskeletal disorders caused are at a high level so that further evaluation and corrective action are required.